Theoretical prediction of electronic and optical properties of haft-hydrogenated InN monolayers. (June 2020) - Vo, Dat D.; Vu, Tuan V.; Nhan, Le C.; Nguyen, Chuong V.; Phuc, Huynh V.; Tong, Hien D.; Hoat, D.M.; Hoa, Le T.; Hieu, Nguyen N.
Abstract: In this work, we investigate the electronic and optical properties of two configurations of haft-hydrogenated indium nitride monolayers H–InN and 2H–InN using first-principles calculations. Both H–InN and 2H–InN monolayers are semiconductors with indirect bandgap quite larger than that of pure InN monolayer. When the spin–orbit coupling was included, their bandgap is significantly reduced. Upon the hydrogenation, charge transfers from InN plane to functionalized species H in H–InN while a small amount of charge has been transferred from H atoms to InN plane in 2H–InN monolayer. Haft-hydrogenated InN monolayers can strongly absorb light in a wide range from visible light to infrared which opens possibilities for their application in optoelectronic devices. Highlights: Haft-hydrogenated InN monolayers are indirect semiconductors at equilibrium. Band gaps of H–InN and 2H–InN monolayers are larger than that of pure InN monolayer. There is a difference in the mechanism of charge transferring between H–InN and 2H–InN. Haft-hydrogenated InN monolayers can strongly absorb both the visible and infrared lights.